2021
DOI: 10.1177/00034894211047829
|View full text |Cite
|
Sign up to set email alerts
|

Acute Vocal Fold Paresis and Paralysis After COVID-19 Infection: A Case Series

Abstract: Objective: Evidence demonstrates neurotropism is a common feature of coronaviruses. In our laryngology clinics we have noted an increase in cases of “idiopathic” vocal fold paralysis and paresis in patients with no history of intubation who are recovering from the novel SARS-Cov-2 coronavirus (COVID-19). This finding is concerning for a post-viral vagal neuropathy (PVVN) as a result of infection with COVID-19. Our objective is to raise the possibility that vocal fold paresis may be an additional neuropathic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 6 publications
(8 reference statements)
0
16
0
2
Order By: Relevance
“…At times, the virus has been shown to produce neurological symptoms like anosmia, Guillain–Barre, Bell's palsy, and encephalopathy [ 12 16 ]. In addition, rare cases have been reported of COVID-19-related VCP [ 7 , 17 20 ]. These patients typically develop vocal cord dysfunction at the onset of a COVID-19 infection concurrent with the development of traditional viral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…At times, the virus has been shown to produce neurological symptoms like anosmia, Guillain–Barre, Bell's palsy, and encephalopathy [ 12 16 ]. In addition, rare cases have been reported of COVID-19-related VCP [ 7 , 17 20 ]. These patients typically develop vocal cord dysfunction at the onset of a COVID-19 infection concurrent with the development of traditional viral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Recently, Sarah K. Rapoport et al reported a case series of vocal fold paresis and paralysis after COVID-19 infection, which was thus suggested to have caused by post viral vagal neuropathy. 4 The distinct mechanism is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Rapaport and colleagues (including the senior author, RTS) reported a case series of 16 patients with new-onset dysphonia following COVID-19 infection. 45 All patients were found to have idiopathic VF paresis or paralysis despite having no prior history of intubation. Neuropathy was confirmed by LEMG in some of those patients.…”
Section: Long-term Effects Of Covid On the Voicementioning
confidence: 99%
“…There is an anticipated increase in need for laryngeal surgery such as vocal fold medialization for paresis, repair of intubation injuries (including vocal fold scar, arytenoid joint fixation, laryngeal stenosis repair, and others) for some patients with prolonged intubation. 45 , 46 , 47 …”
Section: Long-term Effects Of Covid On the Voicementioning
confidence: 99%